ANALISIS STRATEGI PENGUATAN KETAHANAN PANGAN BERAS DI KABUPATEN OGAN KOMERING ULU - Ema Pusvita; Sriati Sriati; Dessy Adriani (Universitas Sebelas Maret, 2019)
Analysis of strengthen strategies of food rice security in Ogan Komering Ulu Regency is a bundle strategy to improve food security in dimensions of availability, stability and food access. This research was historical research.It used time series data, during 26 years period. Technique in collecting data used questionnaires. Data analysis used multiple regression analysis and SWOT matrix. Data presents in tables andpicture, as well as narration to interpret the data.The results of research showes that food security conditions in OKU regency still can meet the needs of rice. Adequacy of food availability, stability and access to food in OKU regency has a surplus of rice along 26 years period. This also shows that OKU regency is able to meet the needs of food rice. The factors that affect food security are (1) the availability of food with a variable land area, production and productivity, (2) stability with variable food consumption, food availability and food access, and (3) access to food that is variable income, the price of rice, the price of corn.Strategies undertaken to improve food security are doing expansion field and farming intensification, applying a single policy basic price of grain, local government policy to apply the regulation about land use, developing of farming with institutional concept, diversifying crops, reducing consumption rice, stabilizing food prices, and improving food reserves. It can be concluded thatstrategy of strengthening food security can be improved by implementing capabilities, minimizing shortage, maximizing opportunities, and overcoming the threats. This study suggest that government should follow the concept of food securitydevelopment and implement the strategy.